The Effect of Home Care Service Innovations in Increasing Patient Loyalty and Satisfaction - Yohana Rangga Bela; Joko Sutrisno; Aprin Rusmawati (PT. Griya Eka Sejahtera, 2020)
Background: The increase in health care costs, large budget cuts make home care services a tool to reduce costs and length of care. As a result, home care services have developed into a complex issue and must be addressed with great care if one of the goals is to provide the best possible outcome for each individual. The purpose of this study was to find out